Rapunzel syndrome in an adolescent girl - Pradeep Kajal; Namita Bhutani (Journal of Pediatric Surgery Case Reports, 2020)
Bezoars are masses, which are commonly encountered in patients after stomach surgery or in those with psychiatric problems. These are formed by the accumulation of intraluminal non digestible substances that can lead to obstruction of the stomach and the small intestine. Trichobezoars are concretions formed by accumulation of hair in stomach. Usually, trichobezoar is confined to the stomach. However, rarely there is contiguous extension of trichobezoar through the pylorus into jejunum, ileum and even up to the colon. Such a condition is called the Rapunzel syndrome. The term comes from a story written by the Grimm brothers in 1812 about Rapunzel who was a long-haired maiden. Rapunzel syndrome is an extremely rare complication of a gastric trichobezoar. We hereby, present the case of a 13 years old girl with Rapunzel syndrome due to a very large gastric trichobezoar. The patient had trichotillomania and trichophagia for 11 year prior to presentation. An abdominal computed tomography scan showed a heterogeneous mass occupying the whole stomach cavity with extension into the jejunum. She was subjected to an exploratory laparotomy and gastrotomy. A large dense mass of hair extending up to jejunum was removed. Following surgery, psychiatric consultation was sought to prevent recurrence. Cases of trichobezoar have been reported in literature very infrequently but Rapunzel syndrome is extremely rare and less than 50 cases have been reported in medical literature till date. Trichobezoar is a very rare cause of upper abdominal mass and should be considered if there is a history of impulsive hair pulling. A psychiatric assessment and a long-term follow-up are advocated as a regular part of treatment to prevent recurrence.